2020
DOI: 10.3390/ijerph17082950
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Pharmacological and Non-Pharmacological Interventions on Symptom Management and Quality of Life among Breast Cancer Survivors Undergoing Adjuvant Endocrine Therapy: A Systematic Review

Abstract: Breast cancer survivors need to undergo adjuvant endocrine therapy after completion of curative treatments to prevent disease recurrence. These individuals often experience symptoms which are detrimental to their quality of life (QOL). Implementation of interventions for effective symptom management among these survivors is warranted. This review provides an overview of studies on the effectiveness of the previously developed interventions for breast cancer survivors undergoing adjuvant endocrine therapy on sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 53 publications
1
26
0
Order By: Relevance
“…The quality of the systematic reviews was mixed. Four systematic reviews had critically low quality [27][28][29][30], nine were low quality [31][32][33][34][35][36][37][38][39], 13 moderate quality [40][41][42][43][44][45][46][47][48][49][50][51][52], and seven high quality [53][54][55][56][57][58][59] (Table 1). There were consistent weaknesses within the reviews.…”
Section: Descriptionmentioning
confidence: 99%
See 3 more Smart Citations
“…The quality of the systematic reviews was mixed. Four systematic reviews had critically low quality [27][28][29][30], nine were low quality [31][32][33][34][35][36][37][38][39], 13 moderate quality [40][41][42][43][44][45][46][47][48][49][50][51][52], and seven high quality [53][54][55][56][57][58][59] (Table 1). There were consistent weaknesses within the reviews.…”
Section: Descriptionmentioning
confidence: 99%
“…Eight systematic reviews [28,33,39,[47][48][49][50]59] and three clinical guidelines [61,72,73] reported on physical activity as a self-management strategy for arthralgia. One systematic review [59] and one clinical guideline [61] were rated as high quality.…”
Section: Physical Activitymentioning
confidence: 99%
See 2 more Smart Citations
“…Adjuvant endocrine therapies that involve the use of drugs such as tamoxifen and aromatase inhibitors (AIs), are often administered to breast cancer patients who have completed curative treatments [1]. These therapies serve to prevent the recurrence of oestrogen receptor (ER)-positive breast cancer, potentially via inhibition of oestrogen production or suppression of the tumourinducing effects of oestrogen via its interaction with ER [2][3][4].…”
Section: Introductionmentioning
confidence: 99%